2020
DOI: 10.1371/journal.pone.0234488
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age at menarche and first sexual intercourse on reproductive and behavioural outcomes: A Mendelian randomization study

Abstract: There is substantial variation in the timing of significant reproductive life events such as menarche and first sexual intercourse. Life history theory explains this variation as an adaptive response to an individual's environment and it is important to examine how traits within life history strategies affect each other. Here we applied Mendelian randomization (MR) methods to investigate whether there is a causal effect of variation in age at menarche and age at first sexual intercourse (markers or results of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…In some western countries like Britain, the average age of sexual debut is around 19 years old, while in America, the average age is around 16 years old. 19,21 While in our study, apart from 95.2% of the participants who still had no sexual debut yet, the average age of sexual debut was 17.5 years old for both male and female students, indicating that they normally began their active sexual life when they were freshmen in university. In China, 70% of people had premarital sex in 2012, up from 15% in 1989.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In some western countries like Britain, the average age of sexual debut is around 19 years old, while in America, the average age is around 16 years old. 19,21 While in our study, apart from 95.2% of the participants who still had no sexual debut yet, the average age of sexual debut was 17.5 years old for both male and female students, indicating that they normally began their active sexual life when they were freshmen in university. In China, 70% of people had premarital sex in 2012, up from 15% in 1989.…”
Section: Discussionmentioning
confidence: 60%
“…The average age of sexual debut varies in different countries and cultural contexts. In Europe, America, and China, it was 19, 16, and 17 years old, respectively 19–22 . With the declining age of sexual debut and compromised condom use, young Chinese students are susceptible to sexually transmitted infections including HPV 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Brown & Sear, n.d.). Again using UK data, a Mendelian randomisation study found that menarche was associated with some later life history traits, such as first and last birth, but not others, such as risk-taking behaviour (Lawn et al, 2020). Two further studies, one using US data and one data from Serbia, found little evidence at all for clustering of life events (Sheppard & Van Winkle, 2020) or for the correlations between 'psychometric' and 'biometric' indicators predicted by LHT-P's 'fast-slow continuum' (Međedović, n.d.).…”
Section: Life History Research In Evolutionary Anthropologymentioning
confidence: 99%
“…(26) Additionally, we corroborated the findings of previous MR studies that identified a positive causal relationship between AAM and AFB, ALB and age at menopause, and between AFS and ALB. (59)(60)(61) Many estimates identified in the primary analysis appear consistent across sensitivity analyses that aim to account for biases. However, some results did not persist in sensitivity analyses checking for robustness to sample overlap and winner's curse.…”
Section: Discussionmentioning
confidence: 74%